The PREDEP-SERT study protocol: A 6-month follow-up cohort study of predictors of effectiveness, tolerability and safety of sertraline for depression using Therapeutic Drug Monitoring - Patricio Molero; Covadonga Canga-Espina; Begoña Tapia-Alzuguren; José Pablo Bullard; María del Mar Unceta-González; Enrique Aubá; Jorge M. Núñez-Córdoba; Felipe Ortuño; Azucena Aldaz (PLoS ONE, 2025)
Sertraline is a common first-line pharmacological treatment of Major Depressive Disorder (MDD). There is no established consensus nor clinical guidelines for personalized dose adjustments, which imply risks of toxicity and lack of efficacy. To address these challenges, there is preliminary evidence of the clinical utility of the determination of blood levels of sertraline by means of therapeutic drug monitoring (TDM). Further evidence is needed regarding the optimal therapeutic range of sertraline in terms of an optimal efficacy/tolerability-safety balance, with need of prospective studies on the association between blood concentration of sertraline and clinical outcomes. The PREDEP-SERT study (PREdictors of response in DEPression treated with SERTraline) is a single-center, observational, longitudinal, ambispective cohort study of patients with MDD to investigate the association between blood concentration of sertraline and its effectiveness, tolerability and safety (pre-registered study in Spain, REec number: 0014-2022-OBS, https://reec.aemps.es/reec/observacional/0014-2022-OBS). It adopts wide inclusion and exclusion criteria in order to allow the inclusion of patients that are representative of real-world clinical practice. It includes an exploratory retrospective subcohort and a subsequent 6-month follow-up prospective subcohort, with repeated measures (blood concentrations of sertraline and clinical outcomes) at scheduled timepoints (15 days, 30 days, 60 days, 90 days and 6 months). Relevant clinical, pharmacogenetic and sociodemographic potential predictors, confounders and effect modifiers will be explored. Its primary objective is to prospectively assess the association between blood concentration of sertraline (and the ratio with its metabolite, N-desmethylsertraline) and the intensity of depressive symptoms measured by the Hamilton Depression Rating Scale at 6 months of treatment. Other secondary objectives are to assess the association between blood concentration of sertraline/N-desmethylsertraline and clinical variables of effectiveness (by means of validated clinical scales) and side effects at every timepoint. Its results may elucidate the clinical utility of TDM in the therapeutic management of MDD in a personalized fashion.